Relacja między wynagrodzeniami a wynikami organizacji w literaturze przedmiotu - Majowska, Magdalena; Strużyna, Janusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the presented article the authors referred to the complexity of relationship between compensation and subsequent organizational performance. Particular attention has been paid to the role the compensation system plays in achieving the goals set by the organization. The literature review of the scope in the paper discussed has been presented. As a result, the authors identified two basic research streams and pointed out the directions for future research. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 357-363